ΦΙΛΑΝΘΡΩΠΙΑ, ΤΕΧΝΙΚΗ ΕΚΠΑΙΔΕΥΣΗ ΚΑΙ ΕΡΓΑΤΙΚΑ ΑΤΥΧΗΜΑΤΑ ΣΤΟΝ ΠΕΙΡΑΙΑ ΤΟ ΤΕΛΕΥΤΑΙΟ ΤΡΙΤΟ ΤΟΥ 19ου ΑΙΩΝΑ - ΚΟΚΚΙΝΑΚΗΣ ΓΙΑΝΝΗΣ (Μνήμων, 1999)
John Kokkinakis, Philanthropy, technical education and labour accidentsin Piraeus in the last third of nineteenth century Concern for the relief of poverty, the support and education of orphansand the living conditions of the working classes was in nineteenth centuryGreece a response to complex social phenomena: urbanization and industrialization,the emergence of new types of poverty and unemployment,the forging of class consciousness in the middle and upper socialclasses.This article reviews the formation and activities of the orphanageof E. Zani in Piraeus and the emergence of specialized technical institutionsin this industrial and commercial port. Documents from charitableactivities of the city magistrates enable us to draw useful informationsregarding the urban poor and unemployed population. The economicand social problems related with labour discipline in general and childlabour in particular may explain the importance of the ideological andcompulsory factors mobilized for ensuring social and industrial peace.In this respect, it was crucial to undertake a new approach towardpoverty, work, and leisure and new educational practices embodyingsuch values as discipline, thrift, diligence and respect.